Improving the protection system in the distribution networks integrated with photovoltaic cells by changing the ratio of X/R - Ali, Muhanad N.; Alsmadi, Othman M. K.; Baniyounes, Ali M. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Due to the increased demand for electrical energy, many countries were prompted nowadays to search for new sources. One important source is the photovoltaic energy. However, despite the great benefits of this source, some defects where observed when linking to distribution networks (negative impact on the protection system). Hence, an approach of improving the protection system in distribution networks integrated with photovoltaic cells is presented in this paper. The protection system improvement is proposed by changing the impedance to resistance ratio (X/R) values of the networks cables, which leads to increasing the overcurrent relays' response speed when a fault occurs. A comparative analysis with different cable reactance values was conducted. The electrical transient analyzer program (ETAP) software was used to investigate and validate the effects on the relay’s response times. Amriya Fallujah power station, located in Iraq, was investigated as a case study. Simulation results show that it is possible to increase the response speed of the overcurrent relay by reducing X/R of the network cables. For more validation, the distance relay was used to compare the best improvement results of changing the X/R ratio with the results of changing the type of relay, which also shows the strength of the proposed method.